2020
DOI: 10.1371/journal.pone.0244639
|View full text |Cite
|
Sign up to set email alerts
|

Progression of coronary artery calcification in conventional hemodialysis, nocturnal hemodialysis, and kidney transplantation

Abstract: Introduction Cardiovascular disease is the leading cause of death in end-stage renal disease (ESRD) and is strongly associated with vascular calcification. An important driver of vascular calcification is high phosphate levels, but these become lower when patients initiate nocturnal hemodialysis or receive a kidney transplant. However, it is unknown whether nocturnal hemodialysis or kidney transplantation mitigate vascular calcification. Therefore, we compared progression of coronary artery calcification (CAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies of SNF472, sotatercept, and oral activated charcoal each reported attenuation of VC progression, whereas studies of exercise training, spironolactone, and nicotinamide did not. We did not include in our review other studies which reported effects on VC after changes in kidney replacement therapies, such as several observational studies assessing the effect of kidney transplantation on VC 120 125 and several evaluating changes in VC after commencement of more frequent or longer hours of hemodialysis (such as nocturnal dialysis) 123 , 126 , 127 . These studies have predominantly reported that VC progression is attenuated by both kidney transplantation and nocturnal hemodialysis when compared with continuation of conventional hemodialysis, but not all studies have consistently shown this 119 , 124 , 125 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of SNF472, sotatercept, and oral activated charcoal each reported attenuation of VC progression, whereas studies of exercise training, spironolactone, and nicotinamide did not. We did not include in our review other studies which reported effects on VC after changes in kidney replacement therapies, such as several observational studies assessing the effect of kidney transplantation on VC 120 125 and several evaluating changes in VC after commencement of more frequent or longer hours of hemodialysis (such as nocturnal dialysis) 123 , 126 , 127 . These studies have predominantly reported that VC progression is attenuated by both kidney transplantation and nocturnal hemodialysis when compared with continuation of conventional hemodialysis, but not all studies have consistently shown this 119 , 124 , 125 …”
Section: Discussionmentioning
confidence: 99%
“…We did not include in our review other studies which reported effects on VC after changes in kidney replacement therapies, such as several observational studies assessing the effect of kidney transplantation on VC [120][121][122][123][124][125] and several evaluating changes in VC after commencement of more frequent or longer hours of hemodialysis (such as nocturnal dialysis). 123,126,127 These studies have predominantly reported that VC progression is attenuated by both kidney transplantation and nocturnal hemodialysis when compared with continuation of conventional hemodialysis, but not all studies have consistently shown this. 119,124,125 The strengths of this review include a systematic search of medical databases, with data extraction, analysis, and quality assessment involving two independent reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…Versus Conventional Dialysis (NOCTx) study assessed annualised CAC progression in patients receiving different renal replacement therapy modalities; -renal transplant, peritoneal dialysis, conventional and nocturnal haemodialysis. CAC progression was not significantly different between treatment groups with comparable progression seen in kidney transplantation, conventional and nocturnal haemodialysis over the 3 year follow up period (Jansz TT et al, 2020). Peritoneal dialysis was associated with more CAC progression than haemodialysis as analysed by the square root transformed volume score per year (ΔCAC SQRV) 92 vs 492mm 3…”
Section: The Arterial Calcifications In Nocturnal Haemodialysis and R...mentioning
confidence: 82%
“…A zero score is associated with a high negative predictive value and a low risk of coronary artery disease and events. Jansz et al found median CACS to be higher in haemodialysis patients than those with vs. 58 [0 -254]) CAC predicts cardiovascular risk in CKD (Jansz TT et al, 2020). A score of >400 is highly predictive in identifying significant CAD in the CKD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation